Empirical Correlation of Compressive and Flexural Strengths in 20 Mpa Rigid Pavement Concrete: Effects of Varied Cement Brands and South Sumatra Local Aggregates - Efrilia Rahmadona; Kiki Rizky Amalia; Norca Praditya; Rio Marpen; Anadia Septiani; Muhammad Hanif; Nanda Wulandari (Integrated Science Education Journal, 2026)
Purpose of the study: The study aims to determine empirical conversion coefficients between compressive strength (f'c) and flexural strength (fs) for a 20 MPa rigid pavement concrete design and to evaluate the specific effects of local South Sumatra aggregates combined with three distinct regional cement brands. Methodology: Laboratory experimental methods utilized 18 specimens (9 cylinders, 9 beams). Aggregates underwent sieve analysis, specific gravity testing, and moisture testing in accordance with SNI standards. Mechanical tests used a compressive strength machine and a two-point loading flexural apparatus. Materials comprised Musi River sand, Baturaja gravel, and Baturaja, Tiga Roda, and Dynamix cements. Data analysis used linear regression models. Main Findings: All variations exceeded the 20 MPa design target. Dynamix cement achieved the highest mean compressive strength (26.23 MPa), while Baturaja cement produced the highest mean flexural strength (3.22 MPa). The derived empirical conversion coefficients (fs √f’c) were 0.67 for Baturaja, 0.66 for Tiga Roda, and 0.62 for Dynamix. The collective correlation yielded a linear regression equation of y = 0.0219x + 2.6131 with R² = 0.2731. Novelty/Originality of this study: This study establishes unique, brand-specific empirical conversion factors for pavement concrete formulated with unique South Sumatra regional aggregates. It directly advances existing engineering knowledge by demonstrating how localized combinations of raw materials deviate from generalized national standard formulas, enabling field engineers to confidently perform rapid quality control without resource-intensive on-site beam trial mixes.